1998
DOI: 10.1364/ao.37.000084
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer scale polarimetry studies using a near-field scanning optical microscope

Abstract: We describe a new technique that incorporates polarization modulation into near-field scanning optical microscopy (NSOM) for nanometer scale polarimetry studies. By using this technique, we can quantitatively measure the optical anisotropy of materials with both the high sensitivity of dynamic polarimetry and the high spatial resolution of NSOM. The magnitude and relative orientation of linear birefringence or linear dichroism are obtained simultaneously. To demonstrate the sensitivity and resolution of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…The small size of the source precludes complete polarization, and the ratio of the two polarizations depends upon the numerical aperture of the collection lens. 35 Note that the scales for 1 nm separation are nearly 10 times those at 10 nm. Also shown in the figure is the profile of the z-electric field times its gradient, which will be of interest later.…”
Section: Model Calculationmentioning
confidence: 99%
“…The small size of the source precludes complete polarization, and the ratio of the two polarizations depends upon the numerical aperture of the collection lens. 35 Note that the scales for 1 nm separation are nearly 10 times those at 10 nm. Also shown in the figure is the profile of the z-electric field times its gradient, which will be of interest later.…”
Section: Model Calculationmentioning
confidence: 99%
“…Although in the recent few years significant progress has been made in this field [5,6], and spatially resolved images of e.g. strain induced birefringence showing %150 nm details have been reported [7], we argue that spectroscopic measurements are less trivial.…”
Section: Introductionmentioning
confidence: 83%
“…Also, it has been suggested that the polarization sensitivity is drastically reduced in the near-field regime [13]. Another work, however, reports on a large polarization contrast achievable with a fiber tip [14], although only using a low NA collection objective [7]. Complications might thus arise when performing nRDS in reflection, since incident and reflected light have to pass through the fiber.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…Two experimental approaches have been used to rotate the polarization of the probing light, using PEMs and EOMs. The PEM [50,76] provides a sinusoidal phase change δ ∝ sin(ωt), while the EOM [28,48,77,78] is characterized by a linear phase change δ ∝ ωt. The respective Jones matrices are reported in Table 10.2.…”
Section: Polarization-modulation Snom: Illumination Modementioning
confidence: 99%
“…Finally we note that (10.35) is valid even if the sample has birefringence, as long as the birefringence principal axes are coincident to the dichroism ones. Again, the fiber-induced retardance can be taken into account by removing the sample and acting on the paddles in order to zero the harmonic signals [76]. A procedure similar to the one described for the EOM case can be followed to deconvolute the residual tip dichroism [76], and determine the true retardance or diattenuation properties of the samples.…”
Section: Polarization-modulation Snom: Illumination Modementioning
confidence: 99%